2023
DOI: 10.3390/w15112052
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified TiO2 Photocatalysts as an Alternative Disinfection Approach for Municipal Wastewater Treatment Plant Effluents

Abstract: Among key issues in municipal wastewater treatment plants (MWTP) is the existence of pathogenic bacteria in the discarded effluents. Conventional disinfectants (ozone, UV irradiation, chlorine) have been insufficient in providing safe water due to the development of undesirable and noxious by-products. TiO2 comprises an attractive alternative to conventional methods because of its versatility and recently explored biocidal efficiency. As a result, within the framework of this study, chemically modified, visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The utilized photoreactor possessed a system of four parallel lamps at a distance of 10 cm above each powder's surface [73]. Blacklight lamps of 368 nm, 830 lumens, and an incident light flux equal to 0.184 µmol quanta/s made by Sylvania (Sylvania, Wilmington, NC, USA) were used as the source of UV light, and all the experiments were carried out under ambient temperature conditions.…”
Section: Photocatalytic Activity Study Of the Prepared Zno Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilized photoreactor possessed a system of four parallel lamps at a distance of 10 cm above each powder's surface [73]. Blacklight lamps of 368 nm, 830 lumens, and an incident light flux equal to 0.184 µmol quanta/s made by Sylvania (Sylvania, Wilmington, NC, USA) were used as the source of UV light, and all the experiments were carried out under ambient temperature conditions.…”
Section: Photocatalytic Activity Study Of the Prepared Zno Samplesmentioning
confidence: 99%
“…The absorbance of the ZnO samples prepared in this manner was measured at 554 nm using a Thermo Fisher Scientific Evolution 200 Spectrometer (Thermo Fisher Scientific, Waltham, MA, USA). The C/C 0 ratio, where C represents the concentration of RhB after a specific period of photocatalysis and C 0 is the initial RhB concentration, was determined indirectly by comparing the measured A (absorption at each time) with the initial A (A initial ) [73].…”
Section: Photocatalytic Activity Study Of the Prepared Zno Samplesmentioning
confidence: 99%
“…Adsorption isotherm tests were conducted with TiO 2 dosing concentrations of 0.1, 0.2, 0.5, 1, 2 and 5 g/L. The TiO 2 concentrations, test duration and sampling intervals were all chosen based on previous trials reported for wastewater (Lofrano, G., Libralato, G., Casaburi, A., Siciliano, A., Iannece, P., Guida, M., Pucci, L., Dentice, E.F., Carotenuto, M., n.d.. n.d 624, 461-469. doi:10.1016/j.scitotenv.2017Rivero et al, 2006;Tsoukleris et al, 2023). A 15 ml sample was taken from the beaker with a syringe at regular intervals over the duration of the tests to monitor the adsorbate concentration.…”
Section: Tio 2 Adsorption Testsmentioning
confidence: 99%